IMPLEMENTASI RESTORATIVE JUSTICE SEBAGAI ALTERNATIF PENYELESAIAN TINDAK PIDANA RINGAN DI INDONESIA - Alicia salsabila Theosalim (Jurnal Hukum Adigama, 2022)
In line with the rapid development of the times, it has an impact on increasingly high economic inequality so that this has caused people to do everything they can to make a living. throughout Indonesia, people who are squeezed by the economy commit various minor crimes in order to make a living and their daily needs, therefore criminal acts are increasing, Indonesia needs a settlement of minor criminal cases that do not only focus on imprisonment which in the end only causes over capacity in State Detention Centers and Correctional Institutions and cause the ineffectiveness of the functions of Correctional Institutions. Restorative Justice is an alternative settlement for minor criminal cases that is more concerned with justice for the rights of the parties involved without going through litigation so that cases can be resolved by mediation between victims, perpetrators and related parties so that peace can be achieved and victims' rights can be guaranteed.